2019
DOI: 10.37358/rc.19.10.7586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Essential Oil Mouthwash on Oral Malodour and Periodontal Status in Patient with Special Needs

Abstract: Oral malodour is the general term used to describe disagreeable odor in expired air with psychological component in patients with special needs. The aim of this study is to evaluate the effect of essential oil mouthwash on oral halitosis and periodontal status of patient with special needs. 26 patients aged between 16-45 were enrolled in this single-blind, parallel-group study. Informed consent was obtained. The following parameters were recorded: gingival index, plaque index, organoleptic breath assessment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The clinical studies showed that in case of a failure of a restoration with a glass ionomer it takes place the cracking of the obturation but maintaining a layer of cement adherent to the dental rough structures. The adhesion is better after the conditioning of the dental surfaces with a watery solution of polyacrylic acid [1,3,4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical studies showed that in case of a failure of a restoration with a glass ionomer it takes place the cracking of the obturation but maintaining a layer of cement adherent to the dental rough structures. The adhesion is better after the conditioning of the dental surfaces with a watery solution of polyacrylic acid [1,3,4].…”
Section: Resultsmentioning
confidence: 99%
“…Glass ionomer cements are influenced by different pH saliva [29,30]. As long as the material is tolerated and protected by the tooth structure, resistance to abrasion will be satisfying [1,4]. Selection of restorative materials must be based on knowledge of their wear behavior and the individual needs of each patient [27,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this has led to an increased demand for fixed orthodontic appliances that are both aesthetic and efficient in terms of treatment duration. Dental materials used in the treatment of oral pathology have to fulfill several properties, such as biocompatibility [3,4], homogeneity [5][6][7][8][9][10], strength [2,[11][12][13][14][15][16][17][18][19][20][21], aesthetics [1], corrosion and degradation resistance [22][23][24][25] indifferent of the general status health of the patient [26,27].…”
mentioning
confidence: 99%